Types of publishing houses - Henningsgaard, Per (Routledge, 2020)
This chapter offers three distinct models for surveying the different types of publishing houses: a model based on funding source, a model based on market segment, and a model based on size. The model based on funding source reveals that there are just three main sources of funding that support the activities of the book publishing industry: traditional publishing, dependent publishing, and self-publishing. The model based on market segment refers to the process of dividing the market into smaller segments of customers that share characteristics. In the case of the book publishing industry, these three market segments are trade publishing, educational publishing, and academic and professional publishing. The model based on size represents the third and final model for surveying the different types of publishing houses, and it includes the Big Five, medium to large independent publishing houses, and small independent publishing houses. By offering for the first time a set of internally coherent (rather than anecdotal) models for surveying the different types of publishing houses, this chapter highlights how specific types of publishing houses within each model are favourably disposed towards the publication of particular genres. It also points to the extraordinary number of ways in which literature and the written word are shaped by the industry that brings these texts into existence.